MENGAMANKAN SERANGAN PACKET SNIFFING PADA JARINGAN KOMPUTER MENGGUNAKAN VPN TUNNEL - Rezi Elsya Putra; Nizwardi Jalinusl; Rijal Islami; mohd Iqbal (PRPM STMIK TRIGUNA DHARMA, 2023)
Technological developments greatly affect and control our daily activities. Technological developments were followed by the era of the Industrial Revolution 4.0. In the use of this technology there are not a few threats, so we need an adequate and secure computer network that is a priority, such as packet sniffing attacks. In sending data in a network it is very important to ensure the confidentiality of the data to be sent so that it does not fall into the hands of third parties. So this research has the goal of securing packet sniffing attacks on computer networks using a VPN tunnel. The results of VPN tunnel research can be used to secure packet sniffing from attacks and threats on the right computer networks